HUBUNGAN LAMA PEMAKAIAN KONTRASEPSI SUNTIK DEPO-MEDROXYPROGESTERON ACETATE DENGAN PENINGKATAN BERAT BADAN DI PUSKESMAS PANGKALAN - Azkia Tunissa; Ida Effendi (Jurnal Akta Trimedika, 2024)
Background: The prevalence of weight gain in family planning acceptors is 79.8%, this will cause hypertension heart disease, heart failure, stroke, dyslipidemia and metabolic syndrome. The duration of depo-medroxy prosesteron acetate (DMPA) injectable contraceptive usage has affect on weight gain because of the hormone progesterone stimulates the appetite control center in the hypothalamus. This study aimed to determine the relationship between duration of DMPA usage and the acceptor’s weight gain at Pangkalan Health Community. Methods: This study was an analytic observational design with a cross-sectional approach. The population were family planning acceptors. The sample was family planning acceptors using DMPA injecting drug at the Pangkalan Health Center from August to November 2022 . The sample selection technique was consecutive non-random sampling. Data were obtained through interviews and family planning acceptor cards. Data obtained were analyzed using the Chi-square test and Fisher's exact. Results: This research carried out from 69 respondents whom 69,6% of them have used DMPA for more than a year and 60,9% respondents gaining more than 3 kg. Relationship between the duration of DMPA injectable contraceptive usage and weight gain showed p value = 0.000. Conclusion: There was significant relationship between the duration of DMPA injectable contraceptive usage and weight gain in family planning acceptors at the Pangkalan Community Health Center.